BEBERAPA SENYAWA NON AROMATIS DARI DAUN ANDALAS (Morus macroura Miq.) - A., Yelmida (Jurnal Riset Kimia, 2007)
ABSTRACT Several non aromatic compounds of the leaf Morus macroura Miq. as the rare Indonesian plant has been extracted using n-hexane as an extractant. The soxletation technique was applied in this extraction. The result are separated by fractionation methods of the liquid vacuum chromatographic and continued with the column gravitation chromatographic. The eluent are n-hexane-ethyl acetate are used in the separation method, based on principles of solvent polarity step by step. These separation was monitoring by  thin layer chromatographic. The identification result by spectroscopy ultraviolet, infrared spectroscopy, mass spectroscopy, 1H-NMR  and   13C-NMR , are four compounds found such as hidroxy tridecanil eicosanoic m.p.67-69 oC, long chain n-alkane m.p. 61-62 oC, long chain aliphatic ester m.p. 65-66 oC and wax ester ketone m.p. 68-70oC. Keywords: non aromatic compound, chromatograhphic